(untitled) (International Seven Journal of Health Research, 2024)
The investigation carried out by the committee for the prevention of infant and neonatal deaths is extremely important to understand what made it possible for the death to happen, what is happening to the population and the family. Aiming at the reduction of deaths from preventable causes. For this to happen in a standardized way it is important that the training of professionals is done, correct filling of forms, improving the quality of care to pregnant women, before and after birth, encouraging guidance and autonomy. Objective: To characterize the deaths of newborns from mothers living in Belo Horizonte/MG in the period 2015 to 2019. Methodology: This is a descriptive study with original secondary data made freely available by the Ministry of Health, through the DATASUS Information System and TABNET. Results: Of the 1,041 newborn deaths in BH/MG, it was possible to find the main causes with emphasis on: some disorders originating in the perinatal period and congenital malformation deformities and chromosomal anomalies. Conclusion: Live birth deaths in Belo Horizonte are preventable, monitoring through prenatal consultations, the birth plan, monitoring of the pregnant woman and humanized delivery within the service capable of meeting the pregnant woman’s needs would reduce deaths. In addition to providing reliable data for sizing the public budget and developing strategies that prioritize specific actions for prevention and health promotion.